Identifikasi Faktor-Faktor yang Menyebabkan Sisa Lebih Perhitungan Anggaran (Studi Kasus pada Pemerintah Kota Yogyakarta dan Pemerintah Kabupaten Kulon Progo) - Aziz Rachman Hakim (Master in Accounting Program, 2014)
The condition of the remains of balance budget (SiLPA) occurs annually in almost local governments (LG). To know the exact factors that cause SiLPA, an in-depth research is needed to be done. The aim of this study was to explore the factors that cause SiLPA in LG of Yogyakarta and Kulon Progo. This was a qualitative research study with multiple-case approach. The data of the study was collected through in-depth interview using purposive sampling and snowball sampling. This study was focused on budgeting and budgeting absorption. The results showed that both LG have similarities in the commitment-budgeting and the central government’s policy. Nevertheless, the both LG have difference in the commitment of expenditure realization, moral hazard of revenue’s target determination, the commitment of the community-will, budgeting conservatism, and political condition.